2022
DOI: 10.21037/gs-22-262
|View full text |Cite
|
Sign up to set email alerts
|

Parameters of dual-energy CT for the differential diagnosis of thyroid nodules and the indirect prediction of lymph node metastasis in thyroid carcinoma: a retrospective diagnostic study

Abstract: Background: To further investigate the differential diagnosis of thyroid nodules using dual-energy computed tomography (DECT) and explore the relationship between DECT parameters and lymph node metastasis in thyroid carcinoma for clinical practice, especially difficult diagnosis by routine imaging examination.Methods: A total of 150 patients with thyroid nodules who underwent preoperative DECT and Thyroid Imaging Report and Data System (TIRADS) classification were enrolled in this study, including 96 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…Lee et al (16) reported that 76 patients with thyroid nodules had lower (p< 0.05) DECT-based standardized IC values for malignant thyroid nodules in the arterial phase compared to benign nodules, indicating that spectral CT could be used to assess abnormal iodine levels in patients with thyroid nodules. Similarly, in a retrospective study that included 150 patients with thyroid nodules, benign nodules examined with spectral CT exhibited higher iodine concentrations and standardized IC in the arterial phase, suggesting that IC values from spectral CT are a useful biomarker for differentiating malignant from benign nodules (8). This is generally consistent with our finding that NIC-A was both lower in malignant thyroid nodules and statistically significant in a multifactorial analysis (p< 0.001).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Lee et al (16) reported that 76 patients with thyroid nodules had lower (p< 0.05) DECT-based standardized IC values for malignant thyroid nodules in the arterial phase compared to benign nodules, indicating that spectral CT could be used to assess abnormal iodine levels in patients with thyroid nodules. Similarly, in a retrospective study that included 150 patients with thyroid nodules, benign nodules examined with spectral CT exhibited higher iodine concentrations and standardized IC in the arterial phase, suggesting that IC values from spectral CT are a useful biomarker for differentiating malignant from benign nodules (8). This is generally consistent with our finding that NIC-A was both lower in malignant thyroid nodules and statistically significant in a multifactorial analysis (p< 0.001).…”
Section: Discussionsupporting
confidence: 89%
“…Computed tomography (CT) can also be used to identify thyroid nodules, provide objective images, establish preoperative localization, provide information for diagnosis, and evaluate treatment outcomes. In addition, CT overcomes the drawbacks of US and FNA, including operator dependence and invasive procedures (8). Therefore, CT examinations are increasingly used for preoperative thyroid nodule evaluation.…”
Section: Introductionmentioning
confidence: 99%
“…DS-DECT detects the iodine content of thyroid nodules, and the iodine content in benign nodules exceeds that of malignant nodules, indicating that thyroid lesions have implications for follicular cells and the decreased iodine metabolism in the lesion area. Moreover, DS-DECT allows for in-depth analysis of the lesion by establishing iodine images [ 28 ]. Iodine uptake by thyroid follicular cells within thyroid nodules and adenomas is reduced in the presence of hyperplasia or degeneration of thyroid tissue or incomplete degeneration within the nodule; in malignant nodules, cellular heterogeneity within the lesion is more pronounced, and thyroid follicular cells have a reduced or even absent capacity for iodine uptake [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to achieve a one-to-one correspondence between SDCT and pathology in the selection and evaluation of lymph nodes in clinical practice, which often leads to inconsistent results. Consequently, many studies have sought to obtain relatively stable information by analyzing and extracting the relevant features of primary tumors to predict LNM risk or metastasis ( 17 - 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it is difficult to achieve a one-to-one correspondence between SDCT and pathology in the selection and evaluation of lymph nodes in clinical practice, which often leads to deviations in analysis results. Thus, the prediction of LNM by analyzing the relevant features of the primary tumors instead of the lymph nodes has attracted increasing attention and has proven effective in some malignant tumor lymph node studies ( 17 - 21 ). There are few reports on predicting LNM by exploring the primary cancer foci of NSCLC using SDCT.…”
Section: Introductionmentioning
confidence: 99%